Pengaruh Suplementasi Saccharomyces boulardii terhadap Kejadian Diare pada Balita - Winda Wahyu Pratiwi; Dwi Sarbini (Fakultas Kedokteran, Universitas Andalas, 2022)
Diarrhea is a disease that occurs due to viral or bacterial infection in the digestive tract system. Signs of diarrhea are the stool becomes liquid and the frequency of bowel movements is more than three times a day and is accompanied by blood and mucus or only mucus. Saccharomyces boulardii is a probiotic yeast with proven medicinal benefits, especially in the gastrointestinal tract and antibiotic booster. Objectives: To describe the effect of Saccharomyces boulardii supplementation on the incidence of diarrhea in toddlers. Methods: Literature review method with 11 articles (2011-2021) and the keywords used are